The Incidence of a Tax on Urban Real Property - Simon, Herbert A. (Quarterly Journal of Economics, 1943)
Four different schools now to be found among economists, 398. — Assumptions made here, 399. — Conflicting views where the total demand for houses is inelastic, 400. — Brown's position substantially correct, 401. — But the "partial equilibrium" approach is open to certain objections, 404. — Separability of the tax into a tax on site value and a tax on building value, 405. — Houses in different locations not quantities of a single commodity but different competing commodities, 409. — Summary of conclusions, 411. — Mathematical appendix, 412.